Expanded CUG Repeat RNA Induces Premature Senescence in Myotonic Dystrophy Model Cells - Hasuike, Yuhei; Mochizuki, Hideki; Nakamori, Masayuki (Frontiers in Genetics, 2022)
Myotonic dystrophy type 1 (DM1) is a dominantly inherited disorder due to a toxic gain of function of RNA transcripts containing expanded CUG repeats (CUGexp). Patients with DM1 present with multisystemic symptoms, such as muscle wasting, cognitive impairment, cataract, frontal baldness, and endocrine defects, which resemble accelerated aging. Although the involvement of cellular senescence, a critical component of aging, was suggested in studies of DM1 patient-derived cells, the detailed mechanism of cellular senescence caused by CUGexp RNA remains unelucidated. Here, we developed a DM1 cell model that conditionally expressed CUGexp RNA in human primary cells so that we could perform a detailed assessment that eliminated the variability in primary cells from different origins. Our DM1 model cells demonstrated that CUGexp RNA expression induced cellular senescence by a telomere-independent mechanism. Furthermore, the toxic RNA expression caused mitochondrial dysfunction, excessive reactive oxygen species production, and DNA damage and response, resulting in the senescence-associated increase of cell cycle inhibitors p21 and p16 and secreted mediators insulin-like growth factor binding protein 3 and plasminogen activator inhibitor-1. This study provides unequivocal evidence of the induction of premature senescence by CUGexp RNA in our DM1 model cells.